Integrated PCA & DCT Based Fusion Using Consistency Verification & Non-Linear Enhancement (International Journal of Engineering and Computer Science, 2014)
The image fusion is becoming one of the hottest techniques in image processing. Many image fusion methods have been developed in a number of applications. Many image fusion methods have been developed in a number of applications. The main objective of image fusion is to combine information from multiple images of the same scene in order to deliver only the useful information. The discrete cosine transforms (DCT) based methods of image fusion are more suitable and time-saving in real-time systems using DCT based standards of still image or video. DCT based image fusion produced results but with lesser clarity, less PSNR value and more Mean square error. Therefore the overall objective is to improve the results by combining DCT with PCA and non-linear enhancement. The proposed algorithm is designed and implemented in MATLAB using image processing toolbox. The comparison has shown that the proposed algorithm provides an significant improvement over the existing fusion techniques.